SOLUSI PEMENUHAN PERANGKAT LUNAK STATISTIKA MELALUI OPEN SOURCE & FREE SOFTWARE - Parhusip, Jadiaman (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2014)
Implementation OSCA (Open Source Campus Agreement) in the higher educationenvironment should be supported by all parties. Along with the spirit of the OSCA, Indonesia alsoinitiated the implementation of IGOS (Indonesia Go Open Source), so that the dependence of thesoftware does not happen on one platform only.Statistics Course is actually a very rapid development when viewed from the side of itssoftware development, so that the teaching of this subject should also apply a specific softwareimplementation, in addition to substantive scientific field.Statistica software that is open source is now very much on the market (especially on theInternet) and ready to be downloaded and used immediately. This is only lifted two only (PSPP andR) because of the limitations of the available pages.